A History of Free Verse - Beyers, Chris, 1962- (Book collections on Project MUSE., 2001)
"Chris Beyers's A History of Free Verse examines the most salient and misunderstood aspect of twentieth-century poetry, free verse. Although the form is generally approached as if it were one indissoluble lump, it is actually a group of differing poetic genres proceeding from much different assumptions. Separate chapters on T.S. Eliot, Wallace Stevens, H.D., and William Carlos Williams elucidate many of these assumptions and procedures, while other chapters address more general theoretical questions and trace the continuity of Modern poetics in contemporary poetry." "Taking a historical and aesthetic approach, Beyers demonstrates that many of the forms considered to have been invented in the Modern period actually extend underappreciated traditions."--Jacket